The types and functions of code switching in a thesis defense examination - Usman Kasim; Yunisrina Qismullah Yusuf; Sri Rahayu Jumiati Ningsih (EduLite: Journal of English Education, Literature and Culture, 2019)
This study investigated the acts of code switching by lecturers and student in thesis defence examination at a university in Banda Aceh, Indonesia. The study involved five participants (four lectures and one student) of the English Language Department. Data from recordings were used to analyse the types and functions of code switching that occurred during the defence. The types of code switching were analysed based on Poplack, and the functions of code switching were analysed based on the theories by Gumperz, Hoffman and Holmes. The result showed that there were three types of code switching found in 109 examples during the interactions between the lecturers and the student, they were: intra-sentential switching (77.06%), inter-sentential switching (15.59%), and tag switching (7.33%). In term of the functions of code switching, 10 functions were identified from 68 switches, they were: addressee specification at 22.05%, followed by interjections (16.17%), loanwords (16.17%), message qualifications (11.76%), transfer of the subconscious markers (8.82%), proper names (8.82%), quotations (5.88%), message reiteration (4.41%), personalization versus objectification (2.94%) and specific features of Islamic terms (2.94%) as the least. It can be concluded that in this case, code switching allowed the participants achieve a wide range of important and interesting ends in their discourse during the thesis defence examination.